2020
DOI: 10.7759/cureus.9952
|View full text |Cite
|
Sign up to set email alerts
|

Blood Component Transfusion in Tertiary Care Neonatal Intensive Care Unit and Neonatal Intermediate Care Unit: An Audit

Abstract: Background Neonates admitted in a tertiary neonatal intensive care unit (NICU) require multiple blood transfusions because of extended NICU stay and repeated sampling. The rookie organ systems and miniature blood volumes in the neonate call for regular audits in neonatal blood transfusion practice. Sharing component usage data with the blood bank will prepare them to store components according to demand, thus limiting wastage of components as well as make banks ready to face a shortage in case of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the same way, Hameed et al (15) , reported that (62.9%) received packed red blood cells (PRBCs) followed by (18.6%) received exchange transfusion, (11.4%) received fresh frozen plasma and (7.1%) received platelets. In contrast to Amrutiya et al (16) , out of a total of 1002 transfusions, 37.82% consisted of fresh frozen plasma, 31.34 percent consisted of red cell concentrate, 28.14 percent consisted of platelet concentrate, and 2.70 percent consisted of whole blood.…”
Section: Discussionmentioning
confidence: 75%
“…In the same way, Hameed et al (15) , reported that (62.9%) received packed red blood cells (PRBCs) followed by (18.6%) received exchange transfusion, (11.4%) received fresh frozen plasma and (7.1%) received platelets. In contrast to Amrutiya et al (16) , out of a total of 1002 transfusions, 37.82% consisted of fresh frozen plasma, 31.34 percent consisted of red cell concentrate, 28.14 percent consisted of platelet concentrate, and 2.70 percent consisted of whole blood.…”
Section: Discussionmentioning
confidence: 75%
“…The CSF is available only for Pb [ 35 , 43 ]. The maximum number of transfusions experienced in the neonatal period (first 28 days of life) was about 22 transfusions [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Greater than 80% of the participating blood centers in our study were part of a hospital/ hospital system. (Table 1) The data on transfusion practices in neonates and pediatrics is limited from India, as only a few academic care centers have published their experiences 4–7 . One of the reasons for such inappropriate data is due to highly variable transfusion practice both at the bedside (clinical use of blood) 8 as well as at the blood centers (blood banks) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…(Table 1) The data on transfusion practices in neonates and pediatrics is limited from India, as only a few academic care centers have published their experiences. [4][5][6][7] One of the reasons for such inappropriate data is due to highly variable transfusion practice both at the bedside (clinical use of blood) 8 as well as at the blood centers (blood banks). 9 With recent advancements in transfusion medicine, aliquoting, component therapy, apheresis technology, and new available immune-hematological tests, the variation in blood center practices has widely increased.…”
Section: Introductionmentioning
confidence: 99%